Measurement of the Higgs boson mass in the H → Z Z∗ → 4ℓ and H → γγ channels with √s = 13 TeV pp collisions using the ATLAS detector - Alconada Verzini, María Josefina (2018)
The mass of the Higgs boson is measured in the H → ZZ*→4ℓ and in the H → γγ decay channels with 36.1 fb−1 of proton–proton collision data from the Large Hadron Collider at a centre-of-mass energy of 13 TeV recorded by the ATLAS detector in 2015 and 2016. The measured value in the H → ZZ*→4ℓ channel is <msubsup is="true">mHZZ⁎</msubsup>=124.79±0.37<mspace width="0.25em" is="true"></mspace><mtext is="true">GeV</mtext>, while the measured value in the H → γγ channel is <msubsup is="true">mHγγ</msubsup>=124.93±0.40<mspace width="0.25em" is="true"></mspace><mtext is="true">GeV</mtext>. Combining these results with the ATLAS measurement based on 7 and 8 TeV proton–proton collision data yields a Higgs boson mass of mH = 124.97± 0.24 GeV.